Engineering design : representation and reasoning - Dym, Clive L.; Brown, David C., 1947- (New York : Cambridge University Press, 2012)
"This text demonstrates that symbolic representation, and related problem-solving methods, offer significant opportunities to clarify and articulate concepts of design"--
Machine generated contents note: 1. Framing the issues; 2. Engineering design; 3. Characterizing the design process; 4. Taxonomies of engineering design; 5. Representing designed artifacts; 6. Representing design processes; 7. Where do we go from here?.
Includes bibliographical references and index.
Keywords: Engineering design -- Data processing; Computer-aided engineering; TECHNOLOGY & ENGINEERING / Engineering (General).